Performance studies of ZnO and multi walled carbon nanotubes-based counter electrodes with gel polymer electrolyte for dye-sensitized solar cell - Chew, J. W. *; Khanmirzaei, M. H.; Numan, Arshid *; Fatin, Saiha Omar; Ramesh, K.; Ramesh, S. (Elsevier, 2018)
Counter electrode (CE) is one of the major component which determine the energy conversion efficiency of the dye-sensitized solar cells (DSSCs). Here in, five types of CEs using two different materials were fabricated. Three types are zinc oxide (ZnO) based while other two are multi-walled carbon nanotubes based CEs. The thickness and resistance per cm2 of each CE were measured. The gel polymer electrolyte based on polyacrylonitrile polymer, sodium iodide salt, 1-Hexyl-3-methyl-imidazolium iodide ionic liquid was also prepared. The conductivity studies revealed that the highest ionic conductivity of gel polymer electrolyte was 6.72 mS cm−1 upon incorporation of 100 wt% 1-Hexyl-3-methyl-imidazolium iodide ionic liquid. This gel polymer electrolyte was sandwiched between commercial TiO2 photo-anode and different types of CE to fabricate the DSSCs. The J-V characteristic curves of the DSSCs were obtained and the DSSC characterization parameters were determined. The efficiencies achieved using ZnO and MWCNT-based CEs were ranging from 0.46% to 7.07%. The results demonstrate that ZnO and multi-walled carbon nanotubes are good candidates of CEs for DSSC application.